Aurignacian only? New evidence for a Gravettian component in the lithic and bone industry from Didon´s excavations at Abri Blanchard - Uthmeier, Thorsten; Pasda, Kerstin; Wiesner, Christina-Maria; Lechner, Cornelia (Quartär. Internationales Jahrbuch zur Eiszeitalter- und Steinzeitforschung / International Yearbook for Ice Age and Stone Age Research, 2020)
The article presents for the first time the collection from Didon´s excavations at Abri Blanchard hosted in the Naturhistorische Gesellschaft Nürnberg. Bought by the Gesellschaft in 1912 through the agency of Hugo Obermaier, the material consists of lithic artifacts, artifacts from bone, antler and ivory, personal ornament, faunal remains and pieces of the brecciated archaeological layer(s). The analysis shows that most of the lithic and osseous artifacts fit well into the variability of the Aurignacian. The bone points can formally be attributed to an early Aurignacian, characterized by split-based points, and a later Aurignacian, indicated by the presence of massive-based points. Although Gravettian artifacts have already been identified in one of the collections hosted in other museums, these were restricted to isolated pieces among the osseous industry. The present study for the first time identified not only additional Gravettian pieces among the osseous industry, but at the same time also a small series of Noailles-type burins, several Gravette points, and a bidirectional core alongside a Pavlovian smoother (“Geweihstecher”). The article discusses how these new findings compare to existing hypothesis about the origin of a non-Aurignacian component at the sit